Creep Coefficient for Self-Compacting Concrete (SCC) - SADIKU, Hajdar; KAMBERI, Mazllum; NAFEZI, Gazmend (International Journal of Computational and Experimental Science and Engineering, 2024)
With the development of construction technology, self-compacting concrete has started to be widely used in the construction of buildings. The specific properties of self compacting concrete have made it particularly useful for concreting the structural elements of high-rise buildings. The strains characteristics of concrete are important to know both in the initial stage of concreting and in the long process, in order to take measures to minimize their impact on cracking and reduction of structure elements. In this regard we have conducted an experiment to investigate shrinkage strains and creep strains in reinforced concrete beams as well as the determination of the creep coefficient. Given that the shrinkage and creep strains are together, it is necessary to separate the creep strains from the shrinkage strains to determine the creep coefficient. For the realization of this separation, we have prepared the same samples which have been used for the determination of shrinkage strains and samples which have been inserted into the mechanisms for the realization of adequate force for the determination of the creep strains.